Isolation and Characterisation of Cocoa Protease - Seow, Teck Keong (1992)
This project was initiated with the intent ion of isolating and characterising protease from cocoa beans,Theobroma cacao Linneaus because a greater knowledge of the proteases present in cocoa beans would lead to a better understanding of the problem of inferior cocoa flavour in Malaysian cocoa beans . The ammonium sulphate fractional precipitation method was used to isolate the cocoa protease while the partial purification of the enzyme was achieved by gel filtrat ion through Sephadex G-200. Four fractions precipitated with 0-20%, 20-40%, 40-60% and 60-80% saturations of ammonium sulphate were found to be proteo lytically active against casein . Further studies were conducted on the fractions precipitated with a -20% and 20-40% saturations of ammonium sulphate.Studies on the isolat ion procedure showed that the add it ion of sodiumdodecyl sulphate (SDS )or Triton X-lOa detergents did not enhance the efficiency of the isolation process. Temperature studies showed that both the 0-20% and 20- 40 % fractions have temperature optima of 45-50°C but were unstable at those temperatures. Both fractions possess more than one pH optima against both case in and bovine serum albumin (BSA). The pH optima are in the strong acidic pH and strong alkaline pH ranges. Inhibit or studies showed that both the 0-20% and 20-40% fractions are likely to contain cysteine proteases while not ruling out the presence of a spartic proteases. The passage of the 0-20% fraction through Sephadex G-200 produced two proteolytically active protein peaks designated as Pl and P2 while that of the 20-40% fraction produced five activity peaks which were not well separated. Studies with sodium dodecyl sulphate polyacrylamide gel electrophoresis (SOS-PAGE) showed that the 0-20% fraction was relatively pure and that the Pl peak was likely to be a protein aggregate. The characteristics of the proteases in both fractions strongly indicate that these enzymes do play a role in the production of cocoa flavour and its precursors during cocoa fermentation.